Implementasi Nilai-Nilai Islam Dalam Pengembangan Pendidikan Berwawasan Lingkungan Hidup Bagi Anak Usia Dini di RA UIN Sunan Kalijaga dan Tk Khalifah - Rohinah, Rohinah (Al-Athfal: Jurnal Pendidikan Anak, 2017)
The research analyzes the implementation of Islamic values in the education of environmental conception. The subject of this research are the early childhood of two schools that have different principles. Applied Islamic values in the education of environmental conceptionmake the early childhood not only realize their environment but also keeping the world, hence they realize their environment and the world from now that following Islamic rules. The type of applied the education of environmental conceptioncan be used as alternative method for teacher in teaching. So that they can build Indonesia; a healthy country, by the students’ creativity. The applied this education program should have educative values, participation and constancy. This research shows that the environmental education can be created optimally by different methods which depend on the early childhood’s condition and matters toward continuous development of this country.